Pollinators support the nutrition and income of vulnerable communities - T. P. Timberlake; S. Sapkota; N. M. Saville; A. R. Cirtwill; S. C. Baral; D. R. Bhusal; K. Devkota; S. Giri; H. A. Harris-Fry; D. Joshi; S. Kortsch; S. S. Myers; et al. (Nature, 2026)
Abstract Biodiversity loss threatens human health and welfare through the degradation of ecosystem services like pollination 1–3 . However, without clear mechanistic links between ecosystems and people, these services can remain abstract and intangible. Consequently, it is challenging to predict the effects of environmental degradation on human welfare or to identify effective ecological interventions that improve human lives. Here we record individual-level diets, crop yields, farming income and crop–pollinator interactions in replicate smallholder communities in Nepal to quantify the links among insect pollinators, crop plants and nutrient intake and income of individual families. Insect pollinators were directly responsible for 44% of people’s farming income and more than 20% of their vitamin A, folate and vitamin E intake. We show how declines in local pollinator species are anticipated to exacerbate rates of poverty and micronutrient deficiency in vulnerable communities such as the ones studied here. However, our results demonstrate that management of local pollination services can improve human nutrition and household income. Indeed, abundant pollinators like native honeybees, bumblebees and hoverflies are the most important for sustaining and enhancing nutrient flows. Applied more widely, this approach of linking biodiversity to human health and livelihoods could reveal sustainable new pathways for improving the lives of millions of smallholders worldwide.